Lack of influence of social media on vaccine decision-making by university students in Ireland - Lyndsey E. Moore; Sonja Vucen; Anne C. Moore (Human Vaccines & Immunotherapeutics)
Vaccine hesitancy is a complex, context-specific issue that negatively impacts vaccine uptake. During the COVID-19 pandemic, vaccine mis- and dis-information on social media negatively impacted on COVID-19 vaccine acceptance. University students’ beliefs and behaviors surrounding vaccine decision-making is less studied, but this population is important in disease transmission, vaccine uptake and effectiveness. Here, we surveyed students in a third-level Irish university, in September 2022, when pandemic restrictions had been removed, to primarily determine if their use of, and influence by, mainstream and social media correlated with their willingness to receive a COVID-19 vaccine or any vaccine. We analyzed 151 responses and found no significant correlation between students’ willingness to receive either a COVID-19 vaccine or any vaccine and their use of social media. There were significant links between vaccine acceptance and a range of factors, namely accommodation type, social media behaviors, perceived exposure to vaccine mis- or dis-information and previous vaccine uptake. This study provides a preliminary insight into drivers of university student COVID-19 and general vaccine willingness. It provides initial data, in the context of post-pandemic restrictions, to support further development of interventions to enhance vaccine uptake in third-level students in Ireland.